The effect of microstructure and fatigue on the acoustoelastic response of aerospace materials - Ellwood, Robert (2012)
This thesis presents work relating to the measurement of the nonlinear acoustoelastic response of several materials with respect to microstructure and fatigue life. The nonlinear acoustoelastic response measures the acoustoelastic coefficient of a material. During normal usage components are subject to stresses that while not sufficient to cause fracture cause fatigue, gradually weakening the component. Linear ultrasonic methods have been shown to be poor at detecting fatigue. However, there is evidence that the accumulation of fatigue damage gives the material a nonlinear elastic response that can be probed by ultrasound. A potential technique to monitor fatigue is produced by monitoring changes in the response of nonlinear ultrasonic techniques.